Regulation of SIRT1 and Its Roles in Inflammation - Yang, Yunshu; Liu, Yang; Wang, Yunwei; Chao, Yongyi; Zhang, Jinxin; Jia, Yanhui; Tie, Jun; Hu, Dahai (Frontiers in Immunology, 2022)
The silent information regulator sirtuin 1 (SIRT1) protein, a highly conserved NAD+-dependent deacetylase belonging to the sirtuin family, is a post-translational regulator that plays a role in modulating inflammation. SIRT1 affects multiple biological processes by deacetylating a variety of proteins including histones and non-histone proteins. Recent studies have revealed intimate links between SIRT1 and inflammation, while alterations to SIRT1 expression and activity have been linked to inflammatory diseases. In this review, we summarize the mechanisms that regulate SIRT1 expression, including upstream activators and suppressors that operate on the transcriptional, post-transcriptional, and post-translational levels. We also summarize factors that influence SIRT1 activity including the NAD+/NADH ratio, SIRT1 binding partners, and post-translational modifications. Furthermore, we underscore the role of SIRT1 in the development of inflammation by commenting on the proteins that are targeted for deacetylation by SIRT1. Finally, we highlight the potential for SIRT1-based therapeutics for inflammatory diseases.